Scaling parameter of the lethal effect of mammalian cells based on radiation-induced OH radicals: effectiveness of direct action in radiation therapy. (14th December 2020) - Kusumoto, Tamon; Ogawara, Ryo; Igawa, Kazuyo; Baba, Kentaro; Konishi, Teruaki; Furusawa, Yoshiya; Kodaira, Satoshi
ABSTRACT: We have been studying the effectiveness of direct action, which induces clustered DNA damage leading to cell killing, relative to indirect action. Here a new criterion Direct Ation-Based Biological Effectiveness (DABBLE) is proposed to understand the contribution of direct action for cell killing induced by C ions. DABBLE is defined as the ratio of direct action to indirect action. To derive this ratio, we describe survival curves of mammalian cells as a function of the number of OH radicals produced 1 ps and 100 ns after irradiation, instead of the absorbed dose. By comparing values on the vertical axis of the survival curves at a certain number of OH radicals produced, we successfully discriminate the contribution of direct action induced by C ions from that of indirect action. DABBLE increases monotonically with increasing linear energy transfer (LET) up to 140 keV/μm and then drops, when the survival curves are described by the number of OH radicals 1 ps after irradiation. The trend of DABBLE is in agreement with that of relative biological effectiveness (RBE) of indirect action. In comparison, the value of DABBLE increases monotonically with LET, when the survival curves are described by the number of OH radicals 100 ns after irradiation. This finding implies that the effectiveness of C ion therapy for cancer depends on the contribution of direct action and we can follow the contribution of direct action over time in the chemical phase.